Biological effects of statins in systemic sclerosis: a systematic review and meta-analysis of 323 patients - Mostafa A. Khalifa; Hamzah M. Alghzawi; Shehabeldin S. Anan; Ahmad Al Rifai; Ayah A. Anwar; Hayder Ali Raheem Al-Saedi; Eman Awady; Islam Masood; Mohamed Elsayed Badr; Mohamed Ismail; Obada Muayaid; Omar M. Ahmed; et al. (DARU Journal of Pharmaceutical Sciences, 2026)

Clinical and molecular characterization of myotonia congenita using whole-exome sequencing in Egyptian patients - Nesma M. Elaraby; Hoda A. Ahmed; Heba Dawoud; Neveen A. Ashaat; Ashraf Azmy; Eman Reda Galal; Yasmine Elhusseny; Heba El Awady; Ammal M. Metwally; Engy A. Ashaat (Molecular Biology Reports, 2024)

Factors Defining Human Adipose Stem/Stromal Cell Immunomodulation in Vitro - Marwa Mahmoud; Mazen Abdel-Rasheed; Eman Reda Galal; Rehab R. El-Awady (Stem Cell Reviews and Reports, 2024)
Human adipose tissue-derived stem/stromal cells (hASCs) are adult multipotent mesenchymal stem/stromal cells with immunomodulatory capacities. Here, we present up-to-date knowledge on the impact of different experimental and donor-related factors on hASC immunoregulatory functions in vitro. The experimental determinants include the immunological status of hASCs relative to target immune cells, contact vs. contactless interaction, and oxygen tension. Factors such as the ratio of hASCs to immune cells, the cellular context, the immune cell activation status, and coculture duration are also discussed. Conditioning of hASCs with different approaches before interaction with immune cells, hASC culture in xenogenic or xenofree culture medium, hASC culture in two-dimension vs. three-dimension with biomaterials, and the hASC passage number are among the experimental parameters that greatly may impact the hASC immunosuppressive potential in vitro, thus, they are also considered. Moreover, the influence of donor-related characteristics such as age, sex, and health status on hASC immunomodulation in vitro is reviewed. By analysis of the literature studies, most of the indicated determinants have been investigated in broad non-standardized ranges, so the results are not univocal. Clear conclusions cannot be drawn for the fine-tuned scenarios of many important factors to set a standard hASC immunopotency assay. Such variability needs to be carefully considered in further standardized research. Importantly, field experts’ opinions may help to make it clearer. Graphical Abstract Parameters that promote ASC immunosuppression on immune cells. Activation of immune cells induces their proliferation and differentiation and presence of ASCs modulates/suppresses such consequences. Augmented immunosuppressive effects of ASCs can be introduced in direct contact with the immune cells and via complementing the repeatedly reported experimental settings (texts in grey shapes). Abbreviations: ASCs: adipose tissue-derived stem/stromal cells, IFN-ɤ: Interferon gamma, MLR: Mixed lymphocyte reaction, TNF: Tumor necrosis factor.